Assessing donor countries contribution to the Goals (2005)
Highlights excerpts from a chapter in the report entitled 'Breaking with business as usual : perspectives from civil society in the Commonwealth on the Millennium Development Goals'. Assesses the contribution of Commonwealth Members of the OECD's Development Assistance Committee to MDG8, with particular emphasis on development assistance, trade and debt.
Keywords: DEVELOPMENT AID